Environmental Application with Multi Sensor Network - Ade Silvia Handayani; Nyayu Latifah Husni; Rosmalinda Permatasari (Computer Engineering and Applications Journal, 2020)
This paper aimed to monitor temperature, humidity, and CO gas level using environmental application with multi sensor network (MSN). This system was applied in real life and real time, to be able to obtain data and information through mobile devices and other on internet network. In this research, environmental application is monitored remotely using displays on the web and sensors as device. This research obtained data in outdoor and indoor parking area also with obstacles and without obstacles, so it obtained the results from each of the different environmental conditions.